The role of engaged scholarship and co-production to address urban challenges: a case study of the Cape Town Knowledge Transfer Programme - Miszczak, Sonia (Department of Environmental and Geographical Science, 2016)
The City of Cape Town is under increasing pressure to develop sustainable urban policies and plans to be able to mitigate and prepare for impacts of environmental change. Both city practitioners and academic researchers in Cape Town believe that one knowledge base is not sufficient to attempt to address the 'wicked problems' associated with environmental change, and that there is a need for collaboration among different knowledge types. This case study considers the value of facilitating an engaged interaction between academics and practitioners in order to co-produce knowledge that can be more relevant and useful for addressing sustainable urban planning challenges. A process of qualitative research by means of interviews with practitioners and researchers within the Cape Town Knowledge Transfer Programme revealed that a more engaged interaction between the researchers and the practitioners, who are the likely users of that research, generates more valuable knowledge and solutions for addressing sustainable urban planning challenges. This case study found that the engaged interaction was immeasurably valuable for both of the institutions, as well as the knowledge produced during the interaction, and the individuals involved in it. The results and implications for partnerships between academic researchers and city practitioners is discussed.